2009
DOI: 10.1111/j.1741-3737.2009.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Commitment and Relationship Quality in Sweden and Norway

Abstract: The Scandinavian countries are often cited as examples of countries where cohabitation is largely indistinguishable from marriage. Using survey data from Norway and Sweden (N = 2,923) we analyzed differences between cohabitors and married individuals in relationship seriousness, relationship satisfaction, and dissolution plans. Our analyses reveal that cohabitors overall are less serious and less satisfied with their relationships and are more likely to consider ending their current relationships than are marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(114 citation statements)
references
References 26 publications
(53 reference statements)
6
105
0
3
Order By: Relevance
“…We could imagine that cohabiters who are classified as viewing their union as a prelude to marriage are more similar to married respondents in their views on cohabitation than other types of cohabiters. Prior studies for instance have shown that cohabiting unions in which marital intentions are present are not qualitatively different from married unions (Brown and Booth 1996;Wiik et al 2009). We could also imagine that countries may differ in the extent to which the views on cohabitation and marriage differ by relationship status.…”
Section: Discussionmentioning
confidence: 99%
“…We could imagine that cohabiters who are classified as viewing their union as a prelude to marriage are more similar to married respondents in their views on cohabitation than other types of cohabiters. Prior studies for instance have shown that cohabiting unions in which marital intentions are present are not qualitatively different from married unions (Brown and Booth 1996;Wiik et al 2009). We could also imagine that countries may differ in the extent to which the views on cohabitation and marriage differ by relationship status.…”
Section: Discussionmentioning
confidence: 99%
“…Couples with lower levels of attachment and commitment to a partner may be less likely to marry than to cohabit or live apart, and in turn report lower levels of relationship satisfaction than those who are married. For example, Wiik, Bernhardt, and Noack (2009) find that Swedish and Norwegian cohabiting couples who intend to get married have similar levels of relationship satisfaction to married couples, and only cohabiting couples with no intention to marry their partner have significantly lower levels of relationship satisfaction. We might expect similar patterns for LAT relationships differentiated according to whether they plan to live together or marry in the future.…”
Section: Union Type and Relationship Satisfactionmentioning
confidence: 99%
“…It is probable that fathers have invested more in their children in a long lasting relationship compared with a short one. Although cohabiting parents have long been culturally accepted in Norway (Noack 2010), and fathers in consensual unions have acquired stronger legal ties to their children, the decision to marry may still signal a greater commitment to family life than a consensual union (Wiik et al 2009). Moreover, many fathers in our sample had their children before the strengthening of cohabiting fathers' rights.…”
Section: Factors and Hypothesis In The Current Analysismentioning
confidence: 99%